Development of Green Pavement for Reducing Oxides of Nitrogen (NOx) in the Ambient Air - Dewi, Kania; Khair, Hafizhul; Irsyad, Moh. (Journal of Engineering and Technological Sciences, 2016)
The transportation sector is the biggest contributor to air pollution in Indonesia, especially in metropolitan cities. Gases such as oxides of nitrogen (NOx) are produced during the combustion of fossil fuels in the internal combustion of vehicle engines. Oxides of nitrogen such as nitric oxide (NO) and nitrogen dioxide (NO2) are important air pollutants, because they cause significant harm to human health and play an important role in being precursors of other dangerous pollutants such as photochemical smog. One of the simple ways to reduce NOx concentrations is utilizing a catalytic process involving UV light and semiconductor particles such as TiO2. Illuminated TiO2 UV light is capable of producing an electron (e-) and hole (h-) pair, which initiates a chemical reaction that alters the NOx to become NO3- or NO2-. A field scale paving block reactor coated with TiO2 placed by the roadside was exposed to UV light using various exposure times. The results showed that the sample with a composition of 200 g/m2 TiO2 was capable of adsorbing NOx gas at an average rate of 0.0046 mg/m2/minute. Additional costs due to TiO2 coating for every square meter of paving are IDR 13,180.